Keefektifan Dalam Penerapan Reinforcement Negatif Untuk Anak Tantrum - Nabilla Waviroh; Ari Purnomo Endah Aflahani (JURNAL LENTERA ANAK, 2021)
Toddler age children are children aged 12-36 months, this period is a time when children begin to learn to face disappointment when their desires are not fulfilled. Emotions such as feeling disappointed, sad, and angry are normal things that happen to children, but if these are not handled properly it can lead to the appearance of temper tantrums. This study aims to determine the effectiveness of applying negative reinforcement techniques for children with tantrums. The application of this technique is expected to help parents in dealing with children's emotional problems, namely tantrums can be reduced or even eliminated. The research method used in this study is a case study with a sample of 1 child and 1 mother as respondents as well as the perpetrators of applying negative reinforcement techniques. Based on the results of research, the application of this negative reinforcement technique can reduce tantrum behavior in children, this is shown at the beginning of the implementation of the child screaming for approximately 10-15 minutes until at the end of the implementation or evaluation of the application of this technique the tantrum behavior of screaming children is reduced to 5 minutes. The application of negative reinforcement is effective in reducing tantrum behavior in children.